Mosquitoes as Potential Bridge Vectors of Malaria Parasites from Non-Human Primates to Humans - Verhulst, Niels O.; Smallegange, Renate C.; Takken, Willem (Frontiers in Physiology, 2012)
Malaria is caused by Plasmodium parasites which are transmitted by mosquitoes. Until recently, human malaria was considered to be caused by human-specific Plasmodium species. Studies on Plasmodium parasites in non-human primates (NHPs), however, have identified parasite species in gorillas and chimpanzees that are closely related to human Plasmodium species. Moreover, P. knowlesi, long known as a parasite of monkeys, frequently infects humans. The requirements for such a cross-species exchange and especially the role of mosquitoes in this process are discussed, as the latter may act as bridge vectors of Plasmodium species between different primates. Little is known about the mosquito species that would bite both humans and NHPs and if so, whether humans and NHPs share the same Plasmodium vectors. To understand the vector-host interactions that can lead to an increased Plasmodium transmission between species, studies are required that reveal the nature of these interactions. Studying the potential role of NHPs as a Plasmodium reservoir for humans will contribute to the ongoing efforts of human malaria elimination, and will help to focus on critical areas that should be considered in achieving this goal.